Exploring the Belief in Resurrection of the Me’enit Ethnic Group in Ethiopia - Moges, Andualem Abate (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This study examines the resurrection myth among the Me'enit ethnic group in southwestern Ethiopia. It examines their belief in a place called Mouu, which was created by the deity Tuma and where people live on after death. The study aims to deepen our understanding of the Me'enit cultural and spiritual worldview by examining the origin and persistence of their belief in resurrection. The methodology involves a combination of primary and secondary data collection and analysis. Primary data was collected through interviews, focus group discussions and participant observation within the Me'enit community, while secondary sources were analyzed for additional context. The data was thoroughly analyzed using narrative theory to identify themes and patterns. The findings shed light on the unique resurrection beliefs and practices of the Me'enit, emphasizing the ongoing presence of the resurrection myth and the importance of Mouu in their belief system. This study contributes to the understanding of the Me'enit ethnic group and their myth and offers insights into their beliefs and practices related to resurrection.